G94 Characterising Changes in the in Vivo Rodent Brain Using Magnetic Resonance Spectroscopy. (4th June 2013) - Rodie, M; Welsh, M; Holmes, W; Gallagher, L; Mullin, J; McMillan, M; Macrae, M; Ahmed, F
Abstract : Background: By providing a non-invasive, functional insight, Magnetic Resonance Spectroscopy (MRS) has the potential to provide objective longitudinal data on mammalian brain development. Aim: To assess the sexual dimorphism in rodent brain chemistry and development using in vivo MRS. Methods: 26(19 male) Sprague-Dawley rats were scanned at 6wks and 20(16 male) at 10wks using a 7TMRI scanner. Testosterone concentrations were measured by ELISA. Metabolites were expressed as a ratio to creatine and full width at half-maximum (FWHM) of the water peak was used as a guide to the reliability of the ratios. Results: Median weight in 6wk males (M6) and females (F6), 10wk males (M10) and females (F10) was 197g(range, 142–230), 131g (121–135), 316g(274–365) and 206g(191–210) respectively. Median anogenital distance (AGD) in M6, F6, M10, F10 was 2.46cm (1.89–2.9), 1.17cm(1.04–1.19), 3.25cm(2.8–3.6) and 1.33cm(1.07–1.60). Median serum testosterone in M6 and M10 were 1.33ng/ml (0.23–5.45) and 3.36ng/ml(1.75–8.26). 14 metabolites were identified in the occipitofrontal cortex. FWHM range was within the optimal range at 12–38Hz. In M6, myo-inositol ratios showed a positive association with circulating testosterone (p = 0.04), and AGD was correlated with phosphocreatine (p = 0.033) and glutamate (p = 0.045). There was a difference between M6 and F6 in 3 metabolite ratios: phosphocholine (p = 0.014), lactate (p = 0.046) and NAA (p = 0.005). In addition, in males, there was an increase from 6wks to 10wks in 3 metabolite ratios: taurine (p = 0.025), myo-inositol (p = 0.012) and phosphocholine (p = 0.005). Conclusions: MRS is a reliable tool for studying the brain in maturing rats and may be a useful tool for studying the link between longitudinal changes in sex steroids and brain development.